A further family with congenital renal proximal tubular dysgenesis. Issue 6 (June 1990) - MacMahon, P; Blackie, R A; House, M J; Risdon, R A; Crawfurd, M D
Abstract : A new syndrome of oligohydramnios, Potter's syndrome, and anuric renal failure leading to stillbirth or neonatal death from respiratory failure has recently been described. Histologically, there is renal tubular dysgenesis, especially of the proximal tubules, and apparent glomerular crowding. To date, five families have been reported, in four of which there have been affected sibs and in two parental consanguinity. The disorder is, therefore, thought to be inherited in an autosomal recessive manner.